Hubungan Antara Motivasi Kerja Dengan Komitmen Organisasi Pada Karyawan PT. Suriatama Mahkota Kencana - Sereina Melani Rambe; Nini Sri Wahyuni; Istiana Istiana (Jouska: Jurnal Ilmiah Psikologi, 2023)
This study aims to know the correlation of work motivation and organizational commitment on employees at PT. Suriatama Mahkota Kencana. The hypothesis proposed is that there is the correlation of organizational commitment and employee motivation. This research method is quantitative with correlation design. The subjects in this study were employees at the head office of PT. Suriatama Mahkota Kencana, totaling 40 people. Technique of sampling is purposive sampling. Data was collected using a scale, namely the scale of organizational commitment and work motivation scale. Data analysis is using Product Moment. Based on the results of the product moment analysis with a coefficient value (rxy) = 0.790 with a significant p = 0.000 0.05. These results indicate that the hypothesis proposed in this study is accepted, namely that there is a correlation of organizational commitment and work motivation. That is, the higher the work motivation, the higher the organizational commitment. The magnitude of the determinant coefficient (r2) is 0.634. This shows that work motivation is distributed by 63.40% towards organizational commitment. In this study, the work motivation of employees is classified as moderate with a hypothetical mean of 60.00 and an empirical mean of 64.575. Organizational commitment is also classified as moderate, with a hypothetical mean of 67.500 and an empirical mean of 69.352.